The Nuclear Word Family List: A List of the Most Frequent Family Members, Including Base and Affixed Words. Issue 3 (26th May 2021) - Cobb, Tom; Laufer, Batia
Abstract: This article introduces the NFL7 (Nuclear Family List 7), a list of the 2, 887 most frequent "nuclear" word families, that is, families that include just the most frequent family members and exclude those that constitute less than 7% of family occurrences. The NFL7 was developed by using a dedicated computer program, the Nuclear List Builder (freely available to users). To construct the list, we used that tool to reduce the complete BNC/COCA lists of the 3, 000 most frequent word families from 19, 062 to 7, 293 word types and from 9, 132 to 5, 610 lemmas. Despite this reduction, the NFL7 compares favorably with other lists in terms of text coverage, and it includes a small number of the most frequent derivational affixes. We argue that the nuclearization of the list makes it suitable for nonadvanced learners, for teaching and testing both receptive and productive knowledge, and for instruction in basic morphology. Abstract :